3 T MRI-based measurements for the integrity of the female pelvic floor in 25 healthy nulliparous women - Alt, Céline D.; Hampel, Franziska; Hallscheidt, Peter; Sohn, Christof; Schlehe, Bettina; Brocker, Kerstin A. (Neurourology and urodynamics, 2016)
Aims Measurements indicating a loss of integrity of the levator ani muscle, which is an integral part of the pelvic floor, have been subject of recent studies using translabial ultrasound and 3D-MRI-models. We transferred these measurements into 2D-3 T-MR-images for clinical routine, as it is objective and does not need exhaustive post-processing. Methods The trial was accepted by the local ethics committee. 25 healthy volunteers fulfilled the inclusion criteria and gave written informed consent. Using high-resolution T2-weighted images (TE 5030-7810 ms, TR 88-112 ms, matrix 512, FOV 280-300 mm, ST 2-3 mm), measurements of anteroposterior hiatus (APH), laterolateral hiatus (LLH), hiatal area (HA), hiatal circumference (HC), levator area (LA), maximum muscle thickness (MMT) and levator urethra gap (LUG) were transferred from ultrasound, iliococcygeus width (IW), puborectalis attachment width (PAW), and levator symphysis gap (LSG) were transferred from 3D-MRI-models. We compared our results to previous studies in the literature. Results Mean value was 52.22 ± 6.97 mm for APH, 33.15 ± 4 mm for LLH, 13.22 ± 3.05 cm2 for HA, 14.19 ± 1.61 cm for HC, 7.14 ± 1.85 cm2 for LA, 6.45 ± 2.07 mm for MMT, 19.47 ± 2.38 mm for LUG, 45 ± 3.97 mm for IW, 33.94 ± 3.34 mm for PAW, 20.54 ± 5.29 mm for LSG. Our results for APH, HA, LUG, and with limitations LA, were comparable to the literature, while HC, LLH, and MMT showed anatomical variances. Results for IW and LSG were comparable, but challenging to measure. We newly proposed a cutoff value for PAW. Conclusions 2D-3 T-MRI combines high-resolution images with objective measurements of parameters regarding pelvic floor integrity, without resorting to exhaustive post-processing methods. Our results may provide a good foundation for further 2D-MR-studies. Neurourol. Urodynam. 35:218-223, 2016. © 2014 Wiley Periodicals, Inc.
Published online 12 November 2014
Gesehen am 13.08.2020